2016
DOI: 10.1016/j.devcel.2016.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Keratins Are Going Nuclear

Abstract: Previously thought to reside exclusively in the cytoplasm, the cytoskeletal protein keratin 17 (K17) has been recently identified inside the nucleus of tumor epithelial cells with a direct impact on cell proliferation and gene expression. We comment on fundamental questions raised by this new finding and the associated significance. Everything should be made as simple as possible, but not simpler.Albert Einstein

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 51 publications
5
54
2
Order By: Relevance
“…Based on sequence homology and expression, IFs are grouped into six classes, all of which except lamins form predominantly cytoplasmic assemblies (Schweizer et al 2006;Hobbs et al 2016). Here, we focus on epithelial keratins to examine their contribution to the mechanical resilience of epithelia in conjunction with desmosomes, although desmin and vimentin also interact with desmosomes in cardiac tissue, meningiomal, and arachnoidal cells in which they fulfill analogous functions (Kartenbeck et al 1983(Kartenbeck et al , 1984.…”
Section: Role Of Ifs In Mechanical Stability Composition Assembly Amentioning
confidence: 99%
See 1 more Smart Citation
“…Based on sequence homology and expression, IFs are grouped into six classes, all of which except lamins form predominantly cytoplasmic assemblies (Schweizer et al 2006;Hobbs et al 2016). Here, we focus on epithelial keratins to examine their contribution to the mechanical resilience of epithelia in conjunction with desmosomes, although desmin and vimentin also interact with desmosomes in cardiac tissue, meningiomal, and arachnoidal cells in which they fulfill analogous functions (Kartenbeck et al 1983(Kartenbeck et al , 1984.…”
Section: Role Of Ifs In Mechanical Stability Composition Assembly Amentioning
confidence: 99%
“…EBS is characterized by cytoplasmic keratin aggregates, cytolysis of basal keratinocytes, and bullous lesions following mild trauma to the skin. Although it is recognized that the pathomechanisms contributing to EBS and additional keratinopathies are more complex than originally considered Roth et al 2012;Bohnekamp et al 2015;Hobbs et al 2016;Kumar et al 2016), it is evident that loss of an intact keratin cytoskeleton renders keratinocytes fragile on mild physical stress, shown by KRT5 and KRT14 KO mice (Lloyd et al 1995;Peters et al 2001). Of note, even mutations causing severe disease do not prevent formation of long keratin intermediate filaments (KIFs) in vitro (Herrmann et al 2002), suggesting that mutations and physical stress act at the level of keratin bundling, network organization, dynamics, or by affecting association with other proteins.…”
Section: Human Disease and Mouse Modelsmentioning
confidence: 99%
“…Recently, we determined by high pressure liquid chromatography and tandem mass spectrometry of proteins extracted from microdissected tissue sections, that keratin 17 (K17), a member of the intermediate filament cytoskeleton family, is overexpressed in SCCs of the uterine and cervical mucosa and that the elevated K17 expression in cervical SCCs is predictive of poor clinical outcome . Subsequent work in our laboratory demonstrated that part of the soluble fraction of K17 enters the nucleus of tumor cells to target p27KIP1 for nuclear export and degradation, resulting in sustained cell cycle progression . Given the histologic similarity and the link of a common HPV‐mediated pathogenesis between cervical SCCs and some HNSCCs, it became important to determine whether K17 could also be a prognostic marker for HNSCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas IFs provide cells with mechanical stability, there is mounting evidence indicating that IFs are involved in a range of metabolic, signaling, and regulatory processes that are unrelated to mechanical functions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The vimentin IF has been shown to act as a scaffold for signaling proteins that regulate epithelial mesenchymal transition (EMT), cancer cell invasion, wound healing and tissue repair, tissue aging, as well as inflammatory signaling (3,4,(6)(7)(8)10).…”
mentioning
confidence: 99%